2021
DOI: 10.1051/matecconf/202133402025
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Grain Loss During Harvesting Due to the Rational Distribution of Vehicles

Abstract: The paper deals with the mathematical model of the rational distribution of vehicles, which allows attaching them to a group of combine harvesters during harvesting, depending on the carrying capacity of vehicles, the productivity of combine harvesters and the capacity of grain storage facilities. In addition, it presents a formula which allows determining the required number of vehicles that will deliver grain from a group of combine harvesters. Further the article presents calculations of routes of vehicles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…(2005) reported that in low land rice ( Oryza sativa L.) production, mechanical harvesting operations accounted for 32.6% of total operational energy consumption because of large fuel consumption. Furthermore, significant crop losses can also occur during the harvesting stage due to improper design or varying operational parameters (Bomoi et al., 2022; D. Wang et al., 2021; Esin et al., 2021; Liang et al., 2017; Ndindeng et al., 2021; Priya et al., 2019; Qu et al., 2021; Rajaiah et al., 2018; Rajaiah et al., 2020; Stathers et al., 2020). Patel et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2005) reported that in low land rice ( Oryza sativa L.) production, mechanical harvesting operations accounted for 32.6% of total operational energy consumption because of large fuel consumption. Furthermore, significant crop losses can also occur during the harvesting stage due to improper design or varying operational parameters (Bomoi et al., 2022; D. Wang et al., 2021; Esin et al., 2021; Liang et al., 2017; Ndindeng et al., 2021; Priya et al., 2019; Qu et al., 2021; Rajaiah et al., 2018; Rajaiah et al., 2020; Stathers et al., 2020). Patel et al.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, significant crop losses can also occur during the harvesting stage due to improper design or varying operational parameters (Bomoi et al, 2022;D. Wang et al, 2021;Esin et al, 2021;Liang et al, 2017;Ndindeng et al, 2021;Priya et al, 2019;Qu et al, 2021;Rajaiah et al, 2018;Rajaiah et al, 2020;Stathers et al, 2020). Patel et al (2018) reported total grain losses in the range of 20-25 kg ha -1 as speed of harvesting operation increased from 1.9 to 2.5 km h -1 .…”
Section: Introductionmentioning
confidence: 99%